Structure and Function of the Neural Cell Adhesion Molecule NCAM - Berezin, Vladimir.; Berezin, Vladimir. (Advances in Experimental Medicine and Biology,, 2010)
Adhesive interactions are important for cell trafficking, differentiation, function and tissue formation. In the nervous system, many cell adhesion molecules (CAMs) are involved in migration of neuroblasts, outgrowth and fasciculation of neuronal processes, formation of synapses and rearrangements of synaptic contacts associated with plasticity including learning and memory. More than eighty CAMs were found to be localized at synaptic sites, where they in a regulated manner bridge pre- and postsynaptic specializations thereby modulating synaptic function. Structure and Function of the Neural Cell Adhesion Molecule NCAM describes recent developments concerning structural, functional and possible therapeutic aspects of one particular CAM, the neural cell adhesion molecule (NCAM). NCAM is one of the first identified and most studied CAMs, and this book is the first attempt to collectively summarize our current knowledge of this important cell adhesion molecule.